(3eQGJH GdfMhjjfs - (3YHO GdhGMO Hf Ydj GdMdHj, CHh GdWjH GddZhj, J (B351 (3g` s
(3ChdgG (B:s
(3GeJYfi Gddg HHbGFc s
(3HBNQgG NW GdYdGeI eMeO Hf GdeNdWI JGQjNg SfI (B861 (3hNW GHf YHO GdfhQ hde jPcQ GdeWGdYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B210s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B190 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B244 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs